1995
DOI: 10.2527/1995.7392834x
|View full text |Cite
|
Sign up to set email alerts
|

Follicular atresia in pigs: measurement and physiology.

Abstract: The physiological regulation of follicular atresia was investigated during the early luteal phase after ovulation and during altrenogest-synchronized preovulatory maturation in pigs (gilts). Apoptosis in dispersed granulosa cells was determined by flow cytometry. Apoptotic (A0) cells contain low, subdiploid amounts of DNA fluorescence. Follicles were classified biochemically as atretic or nonatretic based on the percentage of A0 (% A0) cells, atretic with > or = 10%, and nonatretic with < 10% A0 granulosa cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0
3

Year Published

1997
1997
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 32 publications
2
65
0
3
Order By: Relevance
“…However, regulating the release of pituitary hormones is not the only role of GnRH, because in gilts immunised against GnRH the follicles are not able to grow over 1 mm in diameter, even after PMSG administration (Esbenshade, 1987). The concentration of FSH decreases at about the 5th day, and at the same time an elevated level of follicular atresia is observed (Guthrie et al, 1995) (Fig. 1D, E).…”
Section: Folliculogenesis In Cyclic Giltsmentioning
confidence: 93%
See 2 more Smart Citations
“…However, regulating the release of pituitary hormones is not the only role of GnRH, because in gilts immunised against GnRH the follicles are not able to grow over 1 mm in diameter, even after PMSG administration (Esbenshade, 1987). The concentration of FSH decreases at about the 5th day, and at the same time an elevated level of follicular atresia is observed (Guthrie et al, 1995) (Fig. 1D, E).…”
Section: Folliculogenesis In Cyclic Giltsmentioning
confidence: 93%
“…The number of atretic follicles rises up to 50% on day 7. Between days 7 and 15 of the oestrous cycle the percentage of atretic follicles fluctuates between 12 and 73% (Guthrie et al, 1995). This means that follicles grow in groups with intensification of development at the same time, and then atresia follows steadily, suggesting a kind of regularity (Guthrie et al, 1995).…”
Section: Folliculogenesis In Cyclic Giltsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was followed in 1991 by two reports linking apoptosis to the process of follicular atresia in three different vertebrate species in vivo (Hughes and Gorospe, 1991;Tilly et al, 1991), with both studies relying on the occurrence of oligonucleosome formation as an indicator of apoptotic death. With the interest in apoptosis and the ovary refueled by these investigations, the past several years have seen an exponential increase in the number of publications documenting the occurrence of apoptosis in granulosa cells during atresia in all animal species studied to date (reviewed in: Guthrie et al, 1995;Tilly, 1996;Tilly and Ratts, 1996). In addition, many studies utilizing cultured granulosa cells or intact follicles have identified important roles for a wide spectrum of endocrine, paracrine and autocrine factors, such as gonadotropins (Tilly et al, 1992Chun et al, 1994;Tilly and Tilly, 1995), growth factors (Tilly et al, 1992Chun et al, 1994;Luciano et al, 1994), and neuropeptides (Flaws et al, 1995a), in regulating granulosa cell apoptosis during the later stages of follicular development.…”
Section: Apoptosis In the Ovary: A Brief Historical Accountmentioning
confidence: 99%
“…At the biochemical basis atresia follicular cells are aromatase activity loss and the production of estradiol and the reduced secretion of steroid hormones [4], [33].…”
Section: Physiological Basis Of Folliculogenesis In Mammalsmentioning
confidence: 99%